Tanzania's Treasure: Community Empowerment through Sustainable Cultural Heritage Tourism - Bakari, Stephen Jeuma; Ntow-Gyan, Kwame; Dery, Jane; Asamoah, Edwina; Ankor, Peace; Gyeduah, Comfort; Patience, Kyei (Technium Social Sciences Journal, 2024)
Tanzania, rich in history and cultural diversity, has become a prominent destination for cultural heritage tourism. This study aims to explore the impact of cultural heritage tourism on local community empowerment and sustainable development by assessing how cultural heritage tourism serve as a catalyst for socio-economic growth while preserving the nation's unique cultural assets. The research employed a qualitative methodology, utilizing in-depth online interviews with government officials and community stakeholders. Participants were selected through purposive sampling, followed by snowball sampling to ensure a diverse range of perspectives. Interviews were conducted in Swahili and later translated into English for analysis. Thematic and content analysis were used to identify recurring patterns and key insights from the data. Findings indicate that cultural heritage tourism significantly contributes to job creation and economic development in Tanzania, particularly in areas like Serengeti National Park and Bagamoyo Historical Town. However, challenges such as inadequate infrastructure, limited funding for conservation, and insufficient community involvement pose threats to the sustainability of these initiatives. The study highlights the need for comprehensive stakeholder engagement, effective policy frameworks, and community-based initiatives to enhance the positive impacts of cultural heritage tourism. It concludes that cultural heritage tourism holds substantial potential for empowering Tanzanian communities and promoting sustainable development. By fostering community engagement and implementing responsible tourism practices, Tanzania can harness its cultural heritage to achieve long-term socio-economic benefits and preserve its rich cultural legacy.